2002
DOI: 10.1001/jama.288.4.455
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Persistence in Use of Statin Therapy in Elderly Patients

Abstract: Context Knowledge of long-term persistence with 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor (statin) therapy is limited because previous studies have observed patients for short periods of time, in closely monitored clinical trials, or in other unrepresentative settings. Objective To describe the patterns and predictors of long-term persistence with statin therapy in an elderly US population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
505
7
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,025 publications
(559 citation statements)
references
References 39 publications
(47 reference statements)
33
505
7
2
Order By: Relevance
“…Several studies have found age to be related to increased compliance (Sirey, Bruce, Alexopoulos, Perlick, Friedman, & Meyers, 2001;Kim et al, 2002;Senior, Marteau, & Weinman, 2004;Hertz, Unger, & Lustik, 2005). A few studies have found elderly patients to be more noncompliant than their younger counterparts (Benner, Glynn, Mogun, Neuman, Weinstein, & Avorn, 2002;Balbay,Annakkaya, Arbak, Bilgin, & Erbas, 2005). When assessing compliance solely among Medicaid recipients age 65 and over, Monane et al (1996) found that old age was associated with better compliance.…”
Section: E15mentioning
confidence: 99%
“…Several studies have found age to be related to increased compliance (Sirey, Bruce, Alexopoulos, Perlick, Friedman, & Meyers, 2001;Kim et al, 2002;Senior, Marteau, & Weinman, 2004;Hertz, Unger, & Lustik, 2005). A few studies have found elderly patients to be more noncompliant than their younger counterparts (Benner, Glynn, Mogun, Neuman, Weinstein, & Avorn, 2002;Balbay,Annakkaya, Arbak, Bilgin, & Erbas, 2005). When assessing compliance solely among Medicaid recipients age 65 and over, Monane et al (1996) found that old age was associated with better compliance.…”
Section: E15mentioning
confidence: 99%
“…Several studies have characterized the problem of statin discontinuation by identifying subgroups of patients who are at high risk for discontinuing treatment 14, 19, 20, 21, 22. Few studies have described opportunities to re‐initiate statins.…”
Section: Discussionmentioning
confidence: 99%
“…Согласно многочисленным исследованиям [47][48][49][50] от 20 до 40% пациентов, ко-торым были назначены статины, прекращают их прием через 1 год.…”
Section: приверженность лечению статинамиunclassified